Integration of the Manongkah Shellfish Tradition of the Duano Tribe in Science Learning: Innovative Steps for Developing Culture-Based Modules - Ina Lestari; Zulirfan Zulirfan; Evi Suryawati; Yennita Yennita (Proceeding of the International Conference on Social Sciences and Humanities Innovation, 2024)
This research explores the integration of the Duano tribe's shellfish manongkah tradition into science education to develop culturally relevant learning modules. This research aims to address the gap between local wisdom and its application in science learning, increasing students' understanding and appreciation of their cultural heritage. A qualitative approach was used by conducting surveys and interviews with the Duano tribe community and distributing questionnaires to teachers and students in the Indragiri Hilir coastal area as many as 40 respondents. The findings in this research are that the shellfish Manongkah tradition can be integrated into learning. Furthermore, many teachers and students know about the Manongkah Shell tradition, have never carried out culture-based learning, there is a lack of teaching materials at school, and teachers lack understanding of culture-based learning. This research highlights the importance of contextual learning in preserving cultural traditions while providing practical solutions to today's educational challenges. In conclusion, to overcome this problem, it is necessary to develop a science learning module based on the Manongkah Shellfish tradition so that apart from overcoming this problem, it is hoped that it will be able to improve students' 21st century skills.